Expression of lipocortins in human bronchial epithelial cells: effects of IL-1β , TNF-α, LPS and dexamethasone - M. M. Verheggen; H. I. M. de Bont; P. W. C. Adriaansen-Soeting; B. J. A. Goense; C. J. A. M. Tak; H. C. Hoogsteden; P. Th. W. van Hal; M. A. Versnel (Mediators of Inflammation)
In this study, we investigated the expression of lipocortin I and II (annexin I and I in the human bronchial epithelium, both in vivo and in vitro. A clear expression of lipocortin I and II protein was found in the epithelium in sections of bronchial tissue. In cultured human bronchial epithelial cells we demonstrated the expression of lipocortin I and II mRNA and protein using Northern blotting, FACScan analysis and ELISA. No induction of lipocortin I or II mRNA or protein was observed after incubation with dexamethasone. Stimulation of bronchial epithelial cells with IL-1β, TNF-α or LPS for 24 h did not affect the lipocortin I or II mRNA or protein expression, although PGE2 and 6-keto-PGF1α production was significantly increased. This IL-1β- and LPS-mediated increase in eicosanoids could be reduced by dexamethasone, but was not accompanied by an increase in lipocortin I or II expression. In human bronchial epithelial cells this particular glucocorticoid action is not mediated through lipocortin I or II induction.